Duplex criteria for in‐stent restenosis in the superficial femoral artery. Issue 4 (14th November 2012) - Kawarada, Osami; Higashimori, Akihiro; Noguchi, Miyuki; Waratani, Naoto; Yoshida, Masafumi; Fujihara, Masahiko; Yokoi, Yoshiaki; Honda, Yasuhiro; Fitzgerald, Peter J.
<x xml:space="preserve">Abstract</x> Objectives: To elucidate the optimal cutoff and accuracy of duplex ultrasonography (DUS) parameters for in‐stent restenosis (ISR) after nitinol stenting in the superficial femoral artery (SFA). Background: Few data are available regarding the performance of DUS for binary ISR based on quantitative vessel analysis (QVA) in the era of SFA nitinol stenting. Methods: This retrospective study included 74 in‐stent stenoses of SFA who underwent DUS before follow‐up angiography. DUS parameters, such as peak systolic velocity (PSV) and the peak systolic velocity ratio (PSVR), were compared with percent diameter stenosis (%DS) from a QVA basis. Results: There was a statistically significant correlation (P < 0.001) between "%DS and PSV" and "%DS and PSVR, " and the correlation with %DS proved to be stronger in PSVR (R = 0.720) than in PSV (R = 0.672). The best performing parameter for ISR (50% or greater stenosis) was revealed PSVR, as the areas under the receiver operator characteristics curves using PSVR and PSV were 0.908 and 0.832, respectively. A PSVR cut off value of 2.85 yielded the best predictive value with sensitivity of 88%, specificity of 84%, and accuracy of 86%. The positive predictive value was 85% and the negative predictive value was 88%. Conclusions: A PSVR of 2.85 is the optimal threshold for ISR after nitinol stenting in the SFA. Further large prospective studies are required for the validation and establishment of uniform criteria for DUS parameters. © 2012 Wiley Periodicals, Inc.